Chromothripsis in cancer cells: An update. Issue 10 (30th October 2015) - Rode, Agata; Maass, Kendra Korinna; Willmund, Karolin Viktoria; Lichter, Peter; Ernst, Aurélie
Abstract : In 2011, a novel form of genome instability was reported by Stephens et al ., characterized by tens to hundreds of locally clustered rearrangements affecting one or a few chromosome(s) in cancer cells. This phenomenon, termed chromothripsis, is likely due to a single catastrophic event leading to the simultaneous formation of multiple double‐strand breaks, which are repaired by error‐prone mechanisms. Since then, the occurrence of chromothripsis was detected in a wide range of tumor entities. In this review, we will discuss potential mechanisms of chromothripsis initiation in cancer and outline the prevalence of chromothripsis across entities. Furthermore, we will examine how chromothriptic events may promote cancer development and how they may affect cancer therapy.